Fe doped NiS nanosheet arrays grown on carbon fiber paper for a highly efficient electrocatalytic oxygen evolution reaction. Issue 4 (31st January 2022) - Li, Wenrui; Zhao, Haofei; Li, Hao; Wang, Rongming
Abstract : The microstructure and electronic states of Fe–NiS@CFP are systematically investigated, and it exhibits excellent OER catalytic performance. Abstract : Developing efficient and low-cost non-noble metal catalysts for the oxygen evolution reaction (OER) is important for hydrogen production through water electrolysis. Herein, Fe doped NiS nanosheets directly grown on conductive carbon fiber paper (Fe–NiS@CFP) were fabricated through a two-step hydrothermal process. The microstructure, interface and electronic states of the prepared sample were modulated by Fe doping, exhibiting small internal and interface charge-transfer resistance. Benefiting from these factors, Fe–NiS@CFP shows superior electrocatalytic performance with an overpotential of 275 mV at 100 mA cm −2 and maintains the activity for at least 50 h as a working electrode for the OER. This work may provide insights into the design and fabrication of non-noble metal sulfide electrocatalysts.